1987
DOI: 10.1111/1365-3040.ep11604091
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of neighbour plants by phytochrome perception of spectral changes in reflected sunlight

Abstract: We have tested the hypothesis that a plant may detect the ptesence of a neighbour, befote being shaded by it, thtough the petception of the spectt-al composition of reflected sunlight. Within seedlitig canopies the red : far-red t-atio (R : FR) of the light received by a sensor with a geotnett-y appt-oxitnating that of a stetn was significantly teduced by selective reflection. This effect was observed befote any reduction in the atnount of photosytithetic light energy received by an individual seedling could b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
297
0
14

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 391 publications
(331 citation statements)
references
References 21 publications
11
297
0
14
Order By: Relevance
“…Responses to neighbours via structural crown interaction may be crucial for species composition within communities (Küppers & Lange, 1987;Tremmel & Bazzaz, 1995;Umeki, 1997;Suzuki, 2002). Plants detect neighbours by changes in light quality, and they may alter crown architecture before light availability becomes reduced (Ballaré et al, 1988(Ballaré et al, , 1987. Yokozama et al (1996) pointed out that the difference in crown shapes of conifers (conic) and angiosperm broadleaved trees (spheroidal) may ensure the coexistence of both tree types in boreal and sub-boreal zones.…”
Section: Above-ground Competitionmentioning
confidence: 99%
“…Responses to neighbours via structural crown interaction may be crucial for species composition within communities (Küppers & Lange, 1987;Tremmel & Bazzaz, 1995;Umeki, 1997;Suzuki, 2002). Plants detect neighbours by changes in light quality, and they may alter crown architecture before light availability becomes reduced (Ballaré et al, 1988(Ballaré et al, , 1987. Yokozama et al (1996) pointed out that the difference in crown shapes of conifers (conic) and angiosperm broadleaved trees (spheroidal) may ensure the coexistence of both tree types in boreal and sub-boreal zones.…”
Section: Above-ground Competitionmentioning
confidence: 99%
“…About a decade ago, two studies of the dynamics of plant morphogenesis in seedling stands demonstrated that plants begin responding to the proximity of other plants well before they are shaded by their neighbours (Casal, Sanchez & Deregibus 1986;Ballare et al 1987). Ballare et al (1987Ballare et al ( , 1990 proposed that FR radiation reflected by neighbouring plants played an important role as an early warning signal of competition in growing canopies.…”
Section: Experimental Evidencementioning
confidence: 99%
“…Ballare et al (1987Ballare et al ( , 1990 proposed that FR radiation reflected by neighbouring plants played an important role as an early warning signal of competition in growing canopies. This hypothesis was soon supported by a number of studies that demonstrated the following: (I) plants grown under full sunlight in the field respond to augmented FR radiation with increased elongation and apical dominance (Ballare et al 1987); (2) FR provides a reliable signal of the presence of neighbours well before plants experience a reduction in light availability (e.g.…”
Section: Experimental Evidencementioning
confidence: 99%
“…Seedlings of various species are able to respond to early warning signals of neighbouring plants provided by FR reflected in green tissues (Ballare et al 1987). These R/FR signals anticipate mutual plant shading in growing canopies, i.e.…”
Section: Phytochrome a Is Required For Early Neighbour Detectionmentioning
confidence: 99%